Tree : belief/culture/balance - Lemon, Ralph (Wesleyan University Press ; Eurospan], 2004)
"Tree is the second installment in Ralph Lemon's performance trilogy and documents his travels through India, Indonesia, China, and Japan as he retraces the Buddha's migration map. More artistic sociologist than mere traveler, Lemon kept journals, drew, collected ephermera, conducted informal interviews, and took photograph as he explored performance traditions and met the performers with whom he would eventually choregraph an evening-length work."--BOOK JACKET.